Canine brucellosis in three littermates, case report - Graham, Lindsey T.; Vitale, Samantha N.; Foss, Kari D.; Hague, Devon W.; Anderson, Kimberly M.; Maddox, Carol W. (Frontiers in Veterinary Science, 2022)
Three adult littermates were diagnosed with Brucella canis, two of which were diagnosed with discospondylitis. The first littermate, a 2-year-old spayed-female Labrador Retriever, was evaluated for progressive episodes of cervical pain, lethargy, reported circling to the right, and a right-sided head tilt. Magnetic resonance imaging (MRI) of the cervical spine revealed changes consistent with discospondylitis at C6-C7. MRI of the brain was unremarkable and cerebrospinal fluid analysis was declined. Brucella spp. was isolated from aerobic and Brucella blood cultures. PCR performed on the isolate identified Brucella canis and indirect fluorescent antibody (IFA) testing for Brucella canis also confirmed the species. Patient #1 was treated with doxycycline and marbofloxacin for one year. Clinical signs returned 2-years after diagnosis. Following the diagnosis of patient #1, a known littermate (patient #2) was tested for Brucella canis. Patient #2 was 2 years old and asymptomatic at the time of diagnosis. Aerobic and Brucella spp. cultures, PCR, and IFA were obtained and were diagnostic for Brucella canis. A 6-month course of marbofloxacin and doxycycline was implemented. The patient remained PCR positive following 4 months of treatment and repeat cultures were planned following 6 months of treatment; however, the patient was lost to follow-up. A third littermate (patient #3) was identified by the family of patient #1. Patient #3 was evaluated at 18 months of age for a 6-month history of progressive lumbosacral pain. Spinal radiographs revealed discospondylitis of the C3-C4, T12-T13, and L7-S1 vertebral endplates. Computed tomography (CT) of the lumbosacral spine was also consistent with discospondylitis at L7-S1. Brucella canis serologic testing consisting of rapid slide agglutination test, 2ME-rapid slide agglutination test, and cytoplasmic agar gel immunodiffusion were positive. Enrofloxacin was administered for 7-months, and was discontinued thereafter based on radiographic evidence of healing and resolution of clinical signs. Although Brucella canis is not a rare disease in dogs, the documentation of two out of three adult littermates with associated discospondylitis is an interesting feature. In addition, this report highlights available diagnostic and treatment options, as each patient was managed differently based on clinical signs and preference of the managing clinician.